Comparison of 36 assisted reproduction laboratories monitoring environmental conditions and instrument parameters using the same quality-control application. Issue 1 (July 2019) - Palmer, Giles A; Kratka, Caroline; Szvetecz, Sarah; Fiser, Geraldine; Fiser, Stephen; Sanders, Cody; Tomkin, Giles; Szvetecz, Mary Ann; Cohen, Jacques
Abstract: Research question: Assisted reproduction laboratories record instrument performance periodically. No standardized guidelines have been produced for this activity despite mandatory auditing systems in several countries. This study of 36 laboratories in 12 different countries was conducted to assess differences and similarities between quality assurance programmes using an adaptable cloud-based quality-control app for instrument monitoring. Design: A total of 36 deidentified IVF laboratories that subscribed to the same quality-assurance application were studied. Data were evaluated based on instrument types allocated to 10 domains: incubators, gas tanks, warming surfaces, refrigerators and freezers, cryo-storage, environment, water purification, peripheral equipment, checklists and miscellaneous. Results: The incubator domain constituted the greatest proportion of parameters (35%), followed by surface warming instruments at 15%. Most incubator O2 readings were monitored between 4.5 and 5.5%, and between 5.5 and 6.5% for CO2 . The altitude of the laboratory was poorly correlated with the CO2 setting. Incubator display and measured values of gases and temperature by built-in sensors vary considerably compared with third-party sensors. A quality-control diligence score or mean average data points was calculated for each laboratory. This score is independent of number of instruments or laboratory size. Higher scores were associated with laboratories in countries with government regulations and mandatory auditing systems. Conclusions: Major differences exist in instrument monitoring practices among laboratories. Although incubator monitoring is the largest domain, many other sensitive instruments are diligently monitored by most laboratories. International standardization and guidelines are needed.